2021
DOI: 10.1080/02786826.2021.1947470
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol and droplet generation from performing with woodwind and brass instruments

Abstract: The performing arts have been significantly restricted due to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. We report measurements of aerosol and droplet concentrations generated when playing woodwind and brass instruments and comparisons with breathing, speaking, and singing. These measurements were conducted in a room with zero number concentration aerosol background in the 0.5-20 μm diameter size range, allowing clear attribution of detected particles to specific activities. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 17 publications
9
38
1
Order By: Relevance
“…while breathing and speaking at 70-80 dBA. For both breathing and speaking and across both cohorts, differences in aerosol generation among individuals are lognormally distributed, consistent with previous comparisons of aerosol generation across smaller cohorts [4,31]. Lognormal distribution parameters are provided in electronic supplementary material, table S1.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…while breathing and speaking at 70-80 dBA. For both breathing and speaking and across both cohorts, differences in aerosol generation among individuals are lognormally distributed, consistent with previous comparisons of aerosol generation across smaller cohorts [4,31]. Lognormal distribution parameters are provided in electronic supplementary material, table S1.…”
Section: Resultssupporting
confidence: 80%
“…We note the same observation for children, with statistically significant differences between speaking at 60-70 dBA and 80-90 dBA ( p < 0.001) and between singing at 60-70 dBA and 80-90 dBA ( p < 0.001) for children. This observation is consistent with previous studies noting a volume dependence for vocalization and instrument playing [1,4,31].…”
Section: Comparison Of Aerosol Number and Mass Concentrations From Ch...supporting
confidence: 93%
See 2 more Smart Citations
“…20 The data from this study, however, showed that the aerosol concentration measured at the clarinet's bell to be upwards of 2.4 particles/cm particles/cm 3 in the high note range. 39 The plume generated by playing the clarinet was highly directional, had high velocity, and dispersed quickly, which may lead to discrepancies between the studies. Our results that singing produced more aerosol compared to normal speaking levels are in agreement with Alsved et al (2020).…”
Section: Figure 11 Uhsas and Aps Total Number Concentration For Clarinet Player For The Overlapping Size Range Common Between The Two Insmentioning
confidence: 99%